Analytica chimica acta. - International Union of Pure and Applied Chemistry. Section of Ana lytical Chemistry (Amsterdam, Elsevier.)
"An international journal devoted to all branches of analytical chem istry."
Issued also online.
Vols. 240 and 253 also called of v. 1-2 of: Vibrational spectroscopy .
Keywords: Chemistry, Analytic -- Periodicals; Chemistry, Analytical -- Periodicals